Modelling alpha-diversities of coastal lagoon fish assemblages from the Mediterranean Sea. (July 2018) - Riera, R.; Tuset, V.M.; Betancur-R, R.; Lombarte, A.; Marcos, C.; Pérez-Ruzafa, A.
Highlights: Integration of taxonomic, functional and phylogenetic diversities of Mediterranean coastal lagoons. Ecoregions are crucial to explain fish diversity and, to a lesser extent, other environmental factors. Functional diversity explained better fish assemblage structure. Future conservation studies need to integrate several alpha diversities. Abstract: Coastal lagoons are marine ecosystems spread worldwide with high ecological value; however, they are increasingly becoming deteriorated as a result of anthropogenic activity. Their conservation requires a better understanding of the biodiversity factors that may help identifying priority areas. The present study is focused on 37 Mediterranean coastal lagoons and we use predictive modelling approaches based on Generalized Linear Model (GLM) analysis to investigate variables (geomorphological, environmental, trophic or biogeographic) that may predict variations in alpha-diversity. It included taxonomic diversity, average taxonomic distinctness, and phylogenetic and functional diversity. Two GLM models by index were built depending on available variables for lagoons: in the model 1 all lagoons were used, and in the model 2 only 23. All alpha-diversity indices showed variability between lagoons associated to exogenous factors considered. The biogeographic region strongly conditioned most of models, being the first variable introduced in the models. The salinity and chlorophyll a concentration played a secondary role for the models 1 and 2, respectively. In general, the highest values of alpha-diversities were found in northwestern Mediterranean (Balearic Sea, Alborán Sea and Gulf of Lion), hence they might be considered "hotspots" at the Mediterranean scale and should have a special status for their protection.